Therapy of eserine - Groome, Herbert Revere (My University, 1907)
Introduction: Physostigma,calabar or Ordeal bean is of vegetable origin, its natural habitat being Calabar and region of the mouth of the Niger in West Africa. The parts used are the bean or seed, which is chocolate brown with a broad black groove extending over the entire length of convex edge. The principle constituent of the bean is the alkaloid, Physostigmine or Eserine. There are also the alkaloids Calabarine, a product resulting from the composition of Eserine, and similar in action but weaker; and a neutral principle Physosterine resembling Cholesterine. The official preparation are the fluid extract and tincture of Physostigma, but Physostigmine is most used in Veterinary practice. The forms are the Salicylate and Sulphate, the former being most used as it is more readily dissolved. It is usually given intravenously or subcutaneously.
Citation: Groome, Herbert Revere. Therapy of eserine. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Eserine; Drugs; Effect of Drugs on Body; Medicine; Theses